415PAdult soft tissue myoepithelial carcinoma: Treatment outcomes and efficacy of chemotherapy. (24th November 2019) - Chamberlain, F E; Cojocaru, E; Scaranti, M; Noujaim, J; Thway, K; Fisher, C; Messiou, C; Strauss, D C; Miah, A; Zaidi, S; Benson, C; Gennatas, S; et al.
Abstract: Background: Soft tissue myoepithelial carcinomas are a rare, malignant subgroup of myoepithelial tumours with equal predilection for women and men with most lesions arising in the extremities. The mainstay of management of localised disease is complete surgical resection. Despite optimal treatment 40-45% of tumours recur. Data regarding the efficacy of systemic therapy for advanced and metastatic disease are lacking. The primary aim of this study was to evaluate the outcome of all patients with soft tissue myoepithelial carcinoma treated at a single referral centre. Secondary aims were to establish the efficacy of systemic therapies for patients with advanced disease. Methods: A retrospective review of the prospectively maintained Royal Marsden Sarcoma Unit database to identify soft tissue myoepithelial carcinoma patients treated between 1996 and 2019. Patient baseline characteristics and treatment history were recorded. Response to systemic therapy was evaluated using RECIST 1.1. Results: We identified 24 patients treated at our institution between 1996 and 2019, 12 male and 12 females. Median age at presentation was 49.6 years (interquartile range (IQR) 40.5 – 63.3 years). Twenty-two out of 24 patients (91.7%) underwent primary surgical resection. Nine patients (37.5%) received systemic treatment. A partial response was documented in one patient treated with doxorubicin. Conclusions: Myoepithelial carcinoma frequently recurs after complete surgical resection. Conventional chemotherapy has limited efficacy in this subtype and enrolment in clinical trials should be encouraged. Legal entity responsible for the study: The Royal Marsden NHS Foundation Trust, London, UK. Funding: Has not received any funding. Disclosure: C. Messiou: Honoraria (self): Celgene; Honoraria (self): Janssen. R.L. Jones: Honoraria (self), Advisory / Consultancy: Adaptimmune; Honoraria (self), Advisory / Consultancy: Blueprint; Honoraria (self), Advisory / Consultancy: Clinigen; Honoraria (self), Advisory / Consultancy: Eisai; Honoraria (self), Advisory / Consultancy: Epizyme; Honoraria (self), Advisory / Consultancy: Daichii; Honoraria (self), Advisory / Consultancy: Deciphera; Honoraria (self), Advisory / Consultancy: Immunedesign; Honoraria (self), Advisory / Consultancy: Lilly; Honoraria (self), Advisory / Consultancy: Merck; Honoraria (self), Advisory / Consultancy: PharmaMar. All other authors have declared no conflicts of interest.